Ethnics in coalition: An analysis of stronghold state level party’s performance and trend - Rosmadi Fauzi,; Zulkanain Abdul Rahman,; Mohd Muslim Said,; Muhammad Fathi Marzuki,; Veronica Sayu Balang,; Kamaruzaman Jusoff,; Mohammad Tawfik Yaakub,; Nisfariza Mohd Noor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Pahang was known as Barisan Nasional (BN) stronghold state due to its capabilities to take over the office in Pahang comfortably from the first General Election (GE) until the 13th GE (2013). Despite its triumph, BN Pahang began to lose its tenacity in the 12th GE (2008) and worsened in the 14th GE held in 2018. As a party that consists of three main component parties, namely, United Malays National Organisation (UMNO), Malaysian Chinese Association (MCA), and Malaysian Indian Congress (MIC) needs to devise a new formula and strategy to rebound their position. Therefore, this article was designed to unravel the interrelation between two main keys, ethnicity and alliance formation, to determine the BN resiliency in Pahang. The approach used in this study was a quantitative method using the data obtained from the Election Commission of Malaysia. The data was then tabulated and displayed on a map using the Geographical Information System (GIS). The study found that BN lost their popular vote to the opposing party by only 41.6% compared to 54.8% in the 13th GE. Besides, the number of seats won by BN declined by 39% compared to the 11th GE (2004). Results show that BN needs to form a strong coalition that consists of diversity in terms of ethnicity to win over the office. This study is substantively for parties to win over the electorate’s heart and promote a good democracy in the country.